An overview of environmental sciences and engineering education in Malaysia - Abdullah, A. Hamid; A. Rahman, M. Yaccob Khan; Mohd. Yusoff, Mohd. Rashid (1990)

(untitled)
The important of Environmental Education in borad spectrum has long been acknowledged and recognized throughout the world. Although traits of such education have been evident in the curriculum of a number of subjects at non-tertiary levels, much of the emphasis is often given at teriary levels. The field of Environmental Sciences and Engineering Education rreceived a great impetus since the early 1970s. this could partly be due to the establishment of the Environmental Quality Act of 1974. several Universities offer such courses either as core/trust courses or electives. In the paper, a scenario of the existing Environmental Education System and future projections at all levels are discussed briefly. In addition, the Environmental Sciences and Engineering Education offered at Universiti Teknologi Malaysia in particular is dealt in depth to an extent.